Description of a new species of Eofoersteria Mathot (Hymenoptera: Mymaridae) from India, with a key to world species - Rehmat, Tabassum; Anis, Shoeba Binte (ENTOMON, 2015)
A new species of the genus Eofoersteria Mathot (Hymenoptera: Mymaridae), Eofoersteria manipurensis sp. nov., is described from India, a key to the females of all known species and their distribution is provided.